What Would Next Generation Sequencing Bring to the Diagnosis and Treatment of Sarcomas? A Series of 20 Cases, a Single Institution's Experience - İbrahim KULAÇ; Pınar BULUTAY; Çisel AYDIN MERİÇÖZ (Federation of Turkish Pathology Societies, 2021)
Objective: Soft tissue tumors comprise a small proportion of a pathologist's routine practice. Although morphology and immunohistochemistry are quite helpful for diagnosing these tumors, many require molecular tests. Fluorescence in-situ hybridization has been the most commonly used method for the detection of specific genomic alteration, but next generation sequencing (NGS) could be more informative in many ways. Here we present our targeted NGS experience on soft tissue tumors with a series of 20 cases. Material and Method: The Laboratory Information System (LIS) was screened for soft tissue tumors that had been sequenced by NGS (between January 2018 - February 2021). 20 consecutive cases were included in the study. All cases were sequenced using a commercial targeted sequencing panel designed for soft tissue tumors. Results: We were able to run a reliable sequencing study for 16 (80%) of the cases but 4 (20%) of them failed in quality tests. We have found pathogenic alterations in 12 (60%) of the cases. The most common alterations were EWSR1 fusions, FLI1 being the most common partner. NGS results drastically changed the initial diagnosis, and thus the treatment modalities, in 3 cases (15%): the case with ETV6-NTRK3 fusion, the case with FUS-TFCP2 fusion, and the case of rhabdomyosarcoma (RMS) that was favored to be of the alveolar subtype and turned out to lack FOXO1 fusions. Conclusion: A targeted NGS panel is robust and very informative. It not only allows pathologists to further specify and/or confirm their diagnosis but it could also play an important role in predicting the outcome.